Kill Your Darlings - Krokidas, John; Vachon, Christine; Benaroya, Michael, 1981-; (1973), John Krokidas; (1981), Michael Benaroya; (1989), Daniel Radcliffe; (1982), Jack Huston; (1980), Ben Foster; (1964), David Cross (Demand-Driven Acquisition, 2013)
KILL YOUR DARLINGS is based on true events and characters. For dutiful son ALLEN GINSBERG (Daniel Radcliffe), Columbia University is Mecca"”a portal to art, intellect, culture, and freedom"”everything hometown Patterson, New Jersey is not. When Allen is accepted into Columbia, his father LOUIS (David Cross), a working-class poet, urges him to leave his emotionally ill mother NAOMI (Jennifer Jason Leigh) behind and head to New York to go pursue his own creative dreams. At Columbia, Allen finds stuffy tradition clashing with daringly modern ideas and attitudes"”embodied by LUCIEN CARR (Dane DeHaan), whom he first encounters shouting a scandalous passage from Henry Miller atop a library study table. With his louche charm and androgynous blond beauty, Lucien is an object of fascination for shy, unsophisticated Allen, and soon he is drawn into Lucien's hard-drinking, reefer-smoking, jazz-clubbing circle of friends, including WILLIAM BURROUGHS (Ben Foster), the dissolute scion of a wealthy family, and DAVID KAMMERER (Michael C. Hall), an older hanger-on who clearly resents Allen's position as Lucien's new sidekick. David apparently followed Lucien to New York, and now works as a janitor despite his showy intellectual pretensions. Lucien uses his moody charisma to pit David against Allen while never quite acknowledging his true feelings for either. As their relationship deepens, Allen and Lucien realize they both share emotionally troubled pasts and a passion for poetry. Eager to shatter literary and social conventions, Lucien is full of grandiose manifestos"”but it's Allen whom he challenges to produce the work that will set the world afire (and David who slavishly writes Lucien's school papers). While they're busy competing for his favor, Lucien finds his interest drawn to JACK KEROUAC (Jack Huston), who's older, tougher, and cockier"”a working-class ex-football player who shipped out with the merchant marine, cohabits with sexy EDIE (Elizabeth Olsen) and"”to really up the ante"”writes like a wildman. Jack's oversize persona could easily crush insecure Allen, but instead he encourages Allen's poetry writing. Along with toppling tradition, the "Libertine Circle" "”Lucien, Allen, Jack, and William, with David Kammerer on the outside looking in"”do their best to subvert authority with reckless adventures, enraging college deans and parents alike. For serious student and dutiful son Allen, it's a liberating rebellion, but for obsessed, spurned David, to be excluded is devastating. Devastating"”and deadly. David angrily confronts Lucien, and by the next morning, David's stabbed body has been found in the Hudson River. Lucien's in jail, held for David's murder. And Allen"”begged by Lucien to help him compose his deposition statement"”is struggling to piece together what actually transpired that night in Riverside Park. As Allen peels away Lucien's story of self-defense, he faces a stark choice: to betray himself and lie to the district attorney, supporting Lucien's innocence, or to write the truth"”and condemn his friend. A true story of friendship, love and murder, KYD recounts the pivotal year that changed Allen Ginsberg's life forever and provided the spark for him to start his creative revolution.